A construção do sentido no texto dissertativo-argumentativo em redações do Enem - Costa, Susane da Silva (2018)
This research aims to analyze the construction of meaning in the essay-argumentative text in essays by Enem. The small number of essays with high notes in examination shows the need to investigate this result, since the writing for Enem is a decisive step towards entering higher education. In addition, research on such a construction collaborates to work with the text in the teaching of mother tongue. We start from the hypothesis that the difficulty in producing essay-argumentative texts is related to the absence of the delimitation of a thesis, based on the proposed theme. We base our work on the language approaches developed by Textual Linguistics, based on the works of Koch (1996, 2002, 2007, 2015), Fávero and Koch (2002), Koch and Travaglia (2013), Koch and Elias (2010,2016) and Marcuschi (2005, 2008, 2010, 2012). In analyzing the meaning produced in the essays, especially on the arguments used, we also take as a basis works by Ducrot (1977, 1981, 1987) and Fiorin (2016). The corpus of our research is formed by ten essays by Enem 2015, which texts are divided into two groups with five essays in each one them. The first group consists of essays with with thesis defined and the second, withou tthesis defined. We develop the analysis from two axes: linguistic, textual and semantic elements for the production of meaning in a written text, in formal language situation; and structural organization of the argumentative-essay text. After analyzing the texts, we made a parallel between the two writing groups, trying to define how an Enem writing is configured as a suitable text, based on the evaluation criteria of the Reference Matrix for Writing by Enem (INEP, 2015a). The results obtained prove the initial hypothesis that the lack of elaboration of a thesis makes it difficult the construction of good arguments and, consequently, causes damage to the clarity and the quality of the text produced for Enem. Finally, as writing activy, we suggest an essay proposal focusing on the reader, so that the author builds meaning in the argumentative and dissertation text.